2015
DOI: 10.1097/md.0000000000000926
|View full text |Cite
|
Sign up to set email alerts
|

Association of Endoscopic Sphincterotomy or Papillary Balloon Dilatation and Biliary Cancer

Abstract: Endoscopic sphincterotomy (EST) and endoscopic papillary balloon dilatation (EPBD) have become the main therapeutic procedures in the treatment of biliary and pancreas disease. The risk of cholangiocarcinoma (CCA) is not well investigated among post-EST/EPBD patients with benign diseases, particularly in Asia population.A retrospective nationwide cohort study using data from Taiwan's National Health Insurance Research Database (from January 1, 1998 through December 31, 2010) was conducted. Among patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…ES had been shown to increase biliary epithelial atypia[ 27 ], and previous data have indicated that therapeutic ERCP can increase the subsequent cholangiocarcinoma rate[ 28 ]. At the same time, many recent larger population-based studies have demonstrated that ES does not increase the incidence of cholangiocarcinoma[ 29 - 31 ]. Even some evidence has suggested that ES does not increase the subsequent cholangiocarcinoma rate over that seen with EPBD[ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ES had been shown to increase biliary epithelial atypia[ 27 ], and previous data have indicated that therapeutic ERCP can increase the subsequent cholangiocarcinoma rate[ 28 ]. At the same time, many recent larger population-based studies have demonstrated that ES does not increase the incidence of cholangiocarcinoma[ 29 - 31 ]. Even some evidence has suggested that ES does not increase the subsequent cholangiocarcinoma rate over that seen with EPBD[ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, many recent larger population-based studies have demonstrated that ES does not increase the incidence of cholangiocarcinoma[ 29 - 31 ]. Even some evidence has suggested that ES does not increase the subsequent cholangiocarcinoma rate over that seen with EPBD[ 29 ]. At the same time, cholelithiasis and cholecystectomy had been of concern due to the increase in ICC[ 32 ] and ECC[ 33 ], but some studies have shown that cholecystectomy decreases the subsequent cholangiocarcinoma rate in cholelithiasis patients[ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…A Danish study found a higher incidence of cholangiocarcinoma in the first year after sphincterotomy, but the number of tumors equalized with the control group during long-term follow-up. 19 Other studies from Finland and Sweden, with a large number of patients who underwent sphincterotomy, did not find significant differences in the long-term incidence of tumors compared to the control group. 22 …”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have presented conflicting findings regarding the association between sphincterotomy and the development of biliary and pancreatic neoplasms. 10 , 19 - 21 …”
Section: Discussionmentioning
confidence: 99%
“…18 The details of the NHI programme and the NHIRD have been well documented in previous studies. 16 19 Diseases were coded in the NHIRD according to the 2001 International Classification of Diseases, Ninth revision, Clinical Modification (ICD-9-CM).…”
Section: Methodsmentioning
confidence: 99%